Phytochemical content, especially spermidine derivatives, presenting antioxidant and antilipoxygenase activities in Thai bee pollens - Phanthiwa Khongkarat; Preecha Phuwapraisirisan; Chanpen Chanchao (PeerJ, 2022)
Background Bee pollen (BP) is full of useful nutrients and phytochemicals.Its chemical components and bioactivities depend mainly on the type of floral pollen. Methods Monofloral BP from Camellia sinensis L., Mimosa diplotricha, Helianthus annuus L., Nelumbo nucifera, Xyris complanata, and Ageratum conyzoides were harvested. Crude extraction and partition were performed to yield solvent-partitioned extracts of each BP. Total phenolic content (TPC) was assayed by the Folin-Ciocalteu method, while the flavonoid content (FC) was measured by the aluminium chloride colorimetric method. Antioxidant capacity was measured by the (i) 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, (ii) 2,2’-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) scavenging activity and its Trolox equivalent antioxidant capacity (TEAC), and (iii) ferric reducing antioxidant power (FRAP). All samples were tested for lipoxygenase inhibitory (LOXI) activity. The most active sample was enriched by silica gel 60 column chromatography (SiG60-CC) and high performance liquid chromatography (HPLC), observing the chemical pattern of each fraction using thin layer chromatography. Chemical structure of the most active compound was analyzed by proton nuclear magnetic resonance and mass spectrometry. Results Dichloromethane (DCM)-partitioned BP extracts of H. annuus L. and M. diplotricha (DCMMBP) showed a very high TPC, while DCMMBP had the highest FC. In addition, DCMMBP had the strongest DPPH and ABTS radical scavenging activities (as a TEAC value), as well as FRAP value. Also, DCMMBP (60 µg/mL) gave the highest LOXI activity (78.60 ± 2.81%). Hence, DCMMBP was chosen for further enrichment by SiG60-CC and HPLC. Following this, the most active fraction showed higher antioxidant andLOXI activities with an EC50 for DPPH and ABTS of 54.66 ± 3.45 µg/mL and 24.56 ± 2.99 µg/mL (with a TEAC value of 2,529.69 ± 142.16 µmole TE/g), respectively, and a FRAP value of 3,466.17 ± 81.30 µmole Fe2+/g and an IC50 for LOXI activity of 12.11 ± 0.36 µg/mL. Triferuloyl spermidines were revealed to be the likely main active components. Conclusions TPC, FC, and spermidine derivatives played an important role in the antioxidant and antilipoxygenase activities in M. diplotricha bee pollen.